Thailand - New Dimension Media (Chicagi, Illinois : New Dimension Media, 2005)
'Sometimes known as the'Venice of the East', due to its labyrinth of canals, Bangkok displays a rich history and imperial culture. But there are also many hill tribes in the north of Thailand, where silk weaving, orchid farming, and traditional arts and crafts are witnessed. We see many examples of ancient monumental art and architecture, including the colossal reclining Buddha, and we also experience some of its offshore islands.'--Container
Teacher's guide printed inside container
Grades 6-10 & up
DVD format
Keywords: Thailand -- Geography; Thailand -- History